Kierkegaard and Japanese Thought
XIV, 250 p.
Keywords: Kierkegaard knew nothing of Japanese philosophy yet the links between his own ideas and Japanese philosophers are remarkable. The book examines Kierkegaard in terms of Shinto, Pure Land Buddhism, Zen Buddhism, the Samurai, the famous Kyoto school of Japanese philosophers, and in terms of pivotal Japanese thinkers who were influenced by Kierkegaard.